2023
DOI: 10.3390/ijms24021214
|View full text |Cite
|
Sign up to set email alerts
|

ame-miR-34 Modulates the Larval Body Weight and Immune Response of Apis mellifera Workers to Ascosphara apis Invasion

Abstract: MiRNAs are critical regulators of numerous physiological and pathological processes. Ascosphaera apis exclusively infects bee larvae and causes chalkbrood disease. However, the function and mechanism of miRNAs in the bee larval response to A. apis infection is poorly understood. Here, ame-miR-34, a previously predicted miRNA involved in the response of Apis mellifera larvae to A. apis invasion, was subjected to molecular validation, and overexpression and knockdown were then conducted to explore the regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…In addition, we observed that miR-6001-y putatively targeted as many as 2042 mRNAs, involving Wnt, Hippo, and Jak-STAT signaling pathways, suggesting the involvement of miR-6001-y in adjusting these three signaling pathways of great importance. Additional work such as overexpression and knockdown of miR-6001-y in the larval guts via feeding method, following our previously established protocol [ 36 ], is required to decipher the function and action mechanism of miR-6001-y.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we observed that miR-6001-y putatively targeted as many as 2042 mRNAs, involving Wnt, Hippo, and Jak-STAT signaling pathways, suggesting the involvement of miR-6001-y in adjusting these three signaling pathways of great importance. Additional work such as overexpression and knockdown of miR-6001-y in the larval guts via feeding method, following our previously established protocol [ 36 ], is required to decipher the function and action mechanism of miR-6001-y.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this work and our previous studies demonstrate that miR-6001 as a hub within ceRNA regulatory networks likely exerts a critical function in modulating the larval guts’ growth and development and workers’ midguts in both A. c. cerana and A. m. ligustica . Recently, we established the platforms for dissecting the functions of miRNA [ 36 ] and lncRNA [ 69 ] in bee larval guts. Hence, to identify candidate lncRNAs and circRNAs targeted by ace-miR-6001 and investigate the regulatory functions of the lncRNA-ace-miR-6001 axis and circRNA-ace-miR-6001 axis in the process of the development of larval guts is an interesting and promising direction in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the results demonstrated that TCONS_00032996, TCONS_00032996, and TCONS_00035424 in the workers’ midguts were likely to competitively bind to miR-252 and miR-60 to modulate the mRNA surveillance pathway and DNA replication and repair, further mediating the host response to the infestation by N. ceranae . Recently, we established the technical platform for the functional investigation of honey bee lncRNAs and miRNAs [ 58 , 59 ]. In the near future, we will conduct RNAi of these promising candidate DElnRNAs mentioned above to further explore their ceRNA functions in the response of A. c. cerana workers’ midguts to N. ceranae invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the DEcircRNA-mediated ceRNA network is potentially engaged in regulating the response of A. c. cerana worker larvae to A. apis infection. In the near future, functional dissection of key DEcircRNAs (e.g., RNAi via feeding siRNA targeting back-splicing sites) [71] and miRNAs (overexpression and knockdown via feeding the mimic and inhibitor) [72] will be conducted to explore the ceRNA metabolism underlying the A. c. cerana larval response to A. apis invasion.…”
Section: Discussionmentioning
confidence: 99%